Phantom Limb Pain in Pediatric Oncology - DeMoss, Patrick; Ramsey, Logan H.; Karlson, Cynthia Windham (Frontiers in Neurology, 2018)
Phantom limb pain (PLP) is a prevalent problem for children and adolescents undergoing amputation due to cancer treatment. The symptoms are wide ranging from sharp to tingling. PLP in children typically lasts for a few minutes but can be almost constant, and can be highly distressing. This focused review describes the characteristics, epidemiology, mechanisms, and evidence-based treatment of PLP in pediatric populations, focusing on pediatric cancer. In pediatric oncology, the administration of chemotherapy is a risk factor that potentially sensitizes the nervous system and predisposes pediatric cancer patients to develop PLP after amputation. Gabapentin, tricyclic antidepressants, opiates, nerve blocks, and epidural catheters have shown mixed success in adults and case reports document potential utility in pediatric patients. Non-pharmacologic treatments, such as mirror therapy, psychotherapy, and acupuncture have also been used in pediatric PLP with success. Prospective controlled trials are necessary to advance care for pediatric patients with phantom limb pain.